EY:n direktiivit ja osakesarjojen hintaerot. - Löyttyniemi, Timo. (1992)
EC directives and the price differences between share series.
Summary: EC directives and the price differences between share series.
Keywords: ey; osakkeet; hinnat; äänioikeus; säädökset; aktier; priser (kostnader); rösträtt; författningar; EY